Diversity in the family Isodiametridae (Acoela): New species bring back old problems - Atherton, Sarah; Jondelius, Ulf (Zootaxa, 2022)
Eight new species of Isodiametridae (Acoela) are presented and phylogenetic relationships of the family using 18S and COI sequence data reconstructed. Four species of Baltalimania, two species of Praeaphanostoma and two species of Pseudoposthia are described that all can be distinguished both morphologically and through differences in the DNA sequences as supported by mPTP analysis. The addition of eight new species increases the number of nominal species of Isodiametridae worldwide by 10% and within Sweden by 31%, but also highlights several taxonomic problems. Several species are now confirmed as isodiametrids that are otherwise incongruent with the family’s diagnostic characters. Generic keys are presented for Baltalimania and Praeaphanostoma.